Browsing or buying: A serial mediation analysis of consumer’s online purchase intentions in times of COVID-19 pandemic - Bhatti, Hina Yaqub; Bint E. Riaz, Madiha; Nauman, Shazia; Ashfaq, Muhammad (Frontiers in Psychology, 2022)
The role of digitization and globalization have changed consumers’ online buying behaviors, specifically in the times of the COVID-19 pandemic crisis. This seriously influences the online retail industry in developing countries that are already struggling to move toward digital trading through e-business. Pakistan being a developing country is no exception, and it is, therefore, pertinent to examine factors that contribute to digital trading. Employing theories of reasoned action and the technology acceptance model, this study aims to investigate how personal innovativeness and perceived usefulness impact consumers’ online purchase intentions through a serial mediational model. The data were collected through an online survey from 410 respondents. Structural Equation Modeling (SEM) was used to test the proposed model. This study showed significant results for the direct effect of personal innovativeness and perceived usefulness on online purchase intentions as well as the indirect serial effect via internet browsing and attitude toward online purchasing. The study results have some important practical implications for selling firms, especially in the times of COVID-19. The study suggests that online retailers should be more responsive to the aforementioned factors to facilitate consumers to spend more time browsing, which influences consumers’ interest and intention to make online purchases. As the social distancing and lockdown approaches were implemented in Pakistan and other parts of the world, the trend toward online purchases has increased. Due to this shift in the overall purchasing behavior of consumers and the potential for strong growth in e-commerce, organizations need to consider the post-COVID situation to expand their business in an online platform for addressing the future pandemic crisis.